2022
DOI: 10.3389/fmars.2021.817975
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Site Suitability for Artificial Reefs Deployment in Southeast Coast of India Using Geographical Information System as a Management Tool

Abstract: A planned artificial reef (AR) deployment program as part of a fisheries enhancement might be a useful tool for managers to supplement traditional ways to utilize available space and augment local productivity. Several AR deployment initiatives have been carried out globally, but they are rarely subjected to a rigorous site selection process. We created a site selection procedure in this study that includes systematic stages including exclusion mapping, underwater visual transect, benthic composition, seawater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…A higher load of TSS and a reduction in salinity could be attributed to heavy rainfall (775 mm) in November 2015 compared with the average rainfall (248 mm) in the Nellore coastal region. Furthermore, frequent operation of fishing boats, occasional dredging in shallow coastal mouths, and freshwater input have been reported to increase the TSS load of the water column (Shanthi et al, 2013;Jha et al, 2022), which was observed in the inner stations. The spatial variation of DO was insignificant (p > 0.05, F = 1.5); however, it was significant for BOD (p < 0.05, F = 139).…”
Section: Resultsmentioning
confidence: 99%
“…A higher load of TSS and a reduction in salinity could be attributed to heavy rainfall (775 mm) in November 2015 compared with the average rainfall (248 mm) in the Nellore coastal region. Furthermore, frequent operation of fishing boats, occasional dredging in shallow coastal mouths, and freshwater input have been reported to increase the TSS load of the water column (Shanthi et al, 2013;Jha et al, 2022), which was observed in the inner stations. The spatial variation of DO was insignificant (p > 0.05, F = 1.5); however, it was significant for BOD (p < 0.05, F = 139).…”
Section: Resultsmentioning
confidence: 99%
“…Tamil Nadu has a coastal length of 1076 Km and stretches along the Bay of Bengal, Arabian Sea and the India Ocean. Palk Bay (PB) and the Gulf of Mannar (GoM), which are located along India's southeast coast, form a significant part of of the country's entire coastline length (Barath Kumar et al, 2018;Pandey et al, 2022;Jha et al, 2022). Thanjavur (THA), Pudukottai (PUD), Ramanathapuram (RAM), Thoothukudi (THO), and Tirunelveli (TIR) were five coastal districts (hereafter 'locations') surveyed during the pre monsoon period (January to March) of 2020 to evaluate the seawater quality (Figure 1A).…”
Section: Methodsmentioning
confidence: 99%
“…The ability of diatoms to quickly absorb and store NO 3 − resulted in rapid growth (Cermeno et al, 2011), which could support fisheries by implementing artificial reefs. One earlier study also revealed the importance of fisheries production by maintaining good water quality, productivity and through the deployment of artificial reefs (Jha et al, 2022b).…”
Section: Influence Of Hydrographic Parameters On Phytoplankton Commun...mentioning
confidence: 98%